2023
DOI: 10.18632/aging.205347
|View full text |Cite
|
Sign up to set email alerts
|

Causal effects of lipid-lowering therapies on aging-related outcomes and risk of cancers: a drug-target Mendelian randomization study

Han Chen,
Xinyu Tang,
Wei Su
et al.

Abstract: Background: Despite the widespread use of statins, newer lipid-lowering drugs have been emerging. It remains unclear how the long-term use of novel lipid-lowering drugs affects the occurrence of cancers and age-related diseases. Methods: A drug-target Mendelian randomization study was performed. Genetic variants of nine lipid-lowering drug-target genes ( HMGCR, PCKS9, NPC1L1, LDLR, APOB, CETP, LPL, APOC3 , and ANGPTL3 ) were extracted as exposures from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Ioannou and colleagues suggested that disparities in liver cancer outcomes may stem from varying cholesterol levels in the liver [25]. In another MR study [38], inconsistent findings regarding the impact of PCSK9 inhibitors on tumors, particularly gastric cancer, lung cancer, and hepatocellular carcinoma, were noted. We attribute these differences to two factors: (1) our study used more recent and larger LDL data sets from 2020 and 2022, unlike previous studies that relied on 2013 data, and (2) we employed an additional LDL data set for validation and rigorously excluded reverse causality effects, enhancing the robustness of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Ioannou and colleagues suggested that disparities in liver cancer outcomes may stem from varying cholesterol levels in the liver [25]. In another MR study [38], inconsistent findings regarding the impact of PCSK9 inhibitors on tumors, particularly gastric cancer, lung cancer, and hepatocellular carcinoma, were noted. We attribute these differences to two factors: (1) our study used more recent and larger LDL data sets from 2020 and 2022, unlike previous studies that relied on 2013 data, and (2) we employed an additional LDL data set for validation and rigorously excluded reverse causality effects, enhancing the robustness of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Instrumental Variables (IVs) targeting IL6R were obtained by identifying SNPs in the ±100-kb range of the IL6R locus and are associated with CRP serum levels (association P- value < 5 × 10 −8 ), i.e., they could mimic the effects of IL6R inhibitors since CRP serum levels are a reliable downstream biomarker of IL-6 signaling ( 16 ). To ensure that a sufficient number of SNPs representative of the traits analyzed in this drug-targeted MR analysis were included and to minimize the effect of strong linkage disequilibrium (LD) to a certain extent, we finally fixed the critical value of LD ( r 2 < 0.3) by referring to the literature wherein excellent results have been achieved in the past ( 17 19 ). In addition, to prevent weak instrumental bias, only SNPs with F -statistic >10 were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%